2016
DOI: 10.1177/1420326x16664387
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of health risk and effective dose based on measured radon levels in Korean homes and a qualitative assessment for residents’ radon awareness

Abstract: More than 50% of the worldwide effective radiation dose from natural sources is known to be due to 222 Rn. Indoor radon levels were measured in homes with long-term exposure and in relation to time spent for residents. Measurements were conducted after categorizing homes by type, and the results (mean AE S.D) showed that detached houses, apartments and multifamily houses had radon concentrations of 97 AE 110, 51 AE 24 and 59 AE 34 Bq/m 3 , respectively. Surveys were conducted with 620 people to analyse residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…It is a product of the degradation of uranium and has a radioactive half-life of about four days. Prolonged exposure to elevated radon concentrations has been linked to an increased lung cancer risk [2].…”
Section: Description Of Protocolmentioning
confidence: 99%
“…It is a product of the degradation of uranium and has a radioactive half-life of about four days. Prolonged exposure to elevated radon concentrations has been linked to an increased lung cancer risk [2].…”
Section: Description Of Protocolmentioning
confidence: 99%
“…In 2016, qualitative assessment of the general knowledge level of Korean residents was conducted. In the form of a survey, a total of 620 residents were assessed about their general awareness regarding radon gas (Geon-Woo Lee, 2016). The survey revealed that residents of Korean homes had little awareness regarding the source of radon, exposure routes and contamination levels.…”
Section: Koreamentioning
confidence: 99%
“…The survey revealed that residents of Korean homes had little awareness regarding the source of radon, exposure routes and contamination levels. The excess risk of lung cancer development after exposure for 70 years was determined to be 55 people for every 10,000 people in detached houses located in high radonlevel areas(Geon-Woo Lee, 2016).…”
Section: Koreamentioning
confidence: 99%
“…Lee et al. 26 carried out effective dose based on measured radon levels in Korean homes and a qualitative assessment for residents’ radon awareness. Ali et al.…”
Section: Introductionmentioning
confidence: 99%